Identifying a predictive level of serum C-terminal telopeptide associated with a low risk of medication-related osteonecrosis of the jaw secondary to oral surgery: A systematic review and meta-analysis - Camille Ghio; Robinson Gravier-Dumonceau; Pierre Lafforgue; Roch Giorgi; Thao Pham (PLoS ONE, 2025)
Objective Our aim was to determine serum C-terminal telopeptide of type I collagen (sCTX) thresholds for predicting the minimal risk of medication-related osteonecrosis of the jaw (MRONJ) in patients undergoing anti-resorptive therapy prior to oral surgery. Methods A systematic literature search was conducted in MEDLINE, EMBase, and the Cochrane Library up to September 2023 for case-control, prospective and retrospective studies that assessed sCTX levels in patients exposed to anti-resorptive drugs who underwent oral surgery. We extracted data using a predetermined form. We performed an original percentile meta-analysis method, following PRISMA-DTA guidelines and descriptive analysis to identify the threshold associated with the lowest risk while assessing the overall result of the 95th, 97.5th and 99th percentiles with a random-effect model with weighting by DerSimonian and Laird (RStudio software [v. 4.2.0]). Results Seven studies involving 1281 patients were included. Most patients (96%) were treated for osteoporosis, predominantly with oral bisphosphonates (94.5%). Individual data were available for 58 patients. In the entire population of patients who experienced MRONJ after oral surgery (n = 113), the 95th, 97.5th and 99th percentiles of sCTX were 338.0 pg/mL [95%CI: 190,3; 485,7], 401.9 pg/mL [95%CI: 191,3; 612,6], and 458.0 pg/mL [95%CI: 190,4; 725,6], respectively. Among those treated with oral bisphosphonates for osteoporosis (n = 38), the sCTX 95th, 97.5th and 99th percentiles were 185.3 pg/mL [95%CI: 131,3; 239,3] 187.4 pg/mL [95%CI: 133,9; 240,8] and 188.6 pg/mL [95%CI: 135,4; 241,9], respectively. The determination of these same percentiles with individual data analysis yielded similar results, i.e., 202.0, 257.0 and 260.0 pg/mL. Conclusion This pioneering meta-analysis assesses the risk of MRONJ by analyzing sCTX levels in patients undergoing oral surgery while exposed to antiresorptive drugs. Among patients receiving oral bisphosphonate therapy for osteoporosis, a sCTX threshold of 260 pg/mL is linked to an extremely low risk of MRONJ occurrence, surpassing the 99th percentile. Conversely, for patients undergoing treatment for cancer-related conditions, sCTX levels do not reliably serve as a biomarker for identifying this risk.